The associated volumes of sub-cortical structures and cognitive domain in patients of Mild Cognitive Impairment. (October 2018) - Qian, Lai; Liu, Renyuan; Qin, Ruomeng; Zhao, Hui; Xu, Yun
Highlights: Progress MCI patients had lower scores in memory, language, executive and visual spatial. The volumes of sub-cortical structures in stable MCI and progress MCI patients were heterogeneous. Left hippocampus was predicted region for memory. Left thalamus was predicted region for language, executive and visual spatial. Abstract: This study aimed to explore the relationship between sub-cortical structures alterations and the cognitive domains in Mild Cognitive Impairment (MCI) patients, expected to find identifying sub-cortical structure markers of MCI progression to dementia. A total of 67 MCI patients (8 subjects refused to follow up) were recruited, who were divided into 21 stable MCI (sMCI) and 38 progress MCI (pMCI), according to cognitive assays. FreeSurfer software was used to perform volumetric measurements of the sub-cortical structures from 3.0 T magnetic resonance scans. Data revealed that pMCI subjects had lower scores in memory, language, executive and visual spatial compared with sMCI subjects. Compared with the sMCI group, the volume of the left thalamus, bilateral hippocampus, corpus callosum posterior and corpus callosum central was smaller in pMCI subjects. Partial correlation and general linear regression analysis showed that the left hippocampus was predicted region for memory, left thalamus was predicted region for language, executive and visual spatial. These current results suggest that the volumes of sub-cortical structures in stable MCI and progress MCI patients were heterogeneous. Among these regions, the left hippocampus was predicted region for memory, left thalamus was predicted region for language, executive and visual spatial, suggesting that these structures might be important for detecting the subtle effects of MCI patients' cognitive domain or to assess the effectiveness of therapeutic intervention for MCI.